Budaya di Media Siber: Studi Etnografi Virtual Penggunaan Bahasa Gaul Oleh Generasi Z Pada Aplikasi TikTok - Nurhayati, Iis Kurnia; Putri, Aliyya Rahma (Fakultas Seni Rupa dan Desain ITB, 2024)
Generation Z frequently uses slang as a communication medium for daily conversations due to the proliferation of social media. People typically blend various language variations for communication, whether in real-world interactions or in the virtual realm. One such interaction in the virtual world using slang occurs on the TikTok application, both in content creation and in the comment section. This interaction has transformed slang into a cyberculture, facilitating the exchange of identities in cyberspace. This research utilizes a virtual ethnography approach, incorporating four levels of cyber media analysis, to investigate the usage of slang by Generation Z on the TikTok application at various levels. Through observation and interviews with TikTok content creators and Generation Z users, researchers found several types of slang that have become cultural artifacts on the TikTok application, including slang derived from foreign languages, acronyms, abbreviations, and reversed words, as well as slang borrowed from foreign languages. The interactions occurring on the TikTok application also have real-world effects on the informants, such as experiences, relationships, and changes in daily communication habits due to the presence of slang.